2019
DOI: 10.1523/jneurosci.1958-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Negative Memory Engrams in the Hippocampus Enhance the Susceptibility to Chronic Social Defeat Stress

Abstract: The hippocampus has been highly implicated in depression symptoms. Recent findings suggest that the expression and susceptibility of depression symptoms are related to the enhanced functioning of the hippocampus. We reasoned that hippocampal engrams, which represent ensembles of neurons with increased activity after memory formation, could underlie some contributions of the hippocampus to depression symptoms. Using the chronic social defeat stress model, we examined social defeat-related hippocampal engrams in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 70 publications
(85 reference statements)
1
30
0
Order By: Relevance
“…Given the role of the vHC in modulating affective states, this finding fits with the notion that affective disorders and AUD are comorbid conditions that share circuit plasticity mechanisms 16 , 17 . Indeed chronic stress increases vHC excitability in a manner similar to chronic alcohol exposure 14 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 97%
“…Given the role of the vHC in modulating affective states, this finding fits with the notion that affective disorders and AUD are comorbid conditions that share circuit plasticity mechanisms 16 , 17 . Indeed chronic stress increases vHC excitability in a manner similar to chronic alcohol exposure 14 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 97%
“…BISELLI Et aL. Zhang, Larosa, et al (2019) showed that also negative memory (social defeat related) engram cells in the CA1 region of the hippocampus play a role in vulnerability to stress-induced depressive-like behaviour. Mice susceptible to CSDS in SI testing exhibited a higher reactivation of these engram cells in an additional subsequent social defeat session.…”
mentioning
confidence: 99%
“…In a clinical study in which MRI brain scans were used to detect the volume of hippocampal subregions in depressed patients and healthy control subjects, the left CA1 region emerged as a potential marker of depression 58 . Some studies have shown that the CA1 region is closely related to the pathogenesis of depression models 59 , 60 . Furthermore, in the CNS of adult mammals, neurogenesis mainly occurs in two regions, one of which is the DG.…”
Section: Discussionmentioning
confidence: 99%